Interest rate convergence across maturities: Evidence from bank data in an emerging market economy (2019)
Against a background of financial liberalisation reforms, we assess the extent of market integration and competition in Colombian retail deposits and loans markets. We employ a dataset comprising bank-level interest rate data for different financial products across a range of banks. We utilise and further develop the Phillips and Sul convergence club approach by estimating the drivers of club formation. We find integration of the deposits market, but not loans where portfolio riskiness and loan maturity explain why there is not a fully integrated market. Also, the degree of loan market convergence responds asymmetrically to changes in monetary policy. © 2019 Elsevier Inc.